Green Waterfront City, Future Perspectives for Sustainable City in Tidal Flooding Prone Area at Northern Semarang - Hanif, Ivan Muhammad; Pudyastuti, Purwanti Sri; Sulaiman, Muhammad Isa; Aisyah, Shafara (Dinamika Teknik Sipil: Majalah Ilmiah Teknik Sipil, 2023)
Due to their low topography and flat terrain, Semarang's northern coastal areas are vulnerable to tidal flooding. This paper explains the concept of Green Waterfront City for northern coastal areas of Semarang.  The concepts include: the design of mangrove forest areas on Semarang's North Coast as a natural, eco-friendly barrier that withstands sea abrasion; the concept of an artificial embankment made of natural materials that collects sediment and turns into a dike to reduce sea abrasion; and amphibious housing, which is a versatile, light-colored, eco-friendly residential area. Should the concept be put into practice, it would create advantages in some aspects such as: a) Socially, people affected by the tidal floods on the north coast of Semarang will be provided with appropriate housing and permitted to go back to where they previously lived; b) Economy: Communities affected by tidal floods on Semarang's north coast will see an increase in their economic worth in the fishing and tourism industries through the introduction of Silvofishery; c) Environment: The development of Green Waterfront City for northern coastal areas of Semarang can mitigate the negative environmental effects of tidal flooding and sea abrasion.